Choice of law and jurisdiction in banking and finance contracts after Brexit: a perspective from Europe. Issue 2 (2nd April 2020) - Espar, Oriol; Castell, Jesús
Abstract : English law is the preferred law for banking and finance transactions whether they take place in the United Kingdom or not. When opting for English law to govern a contract, the choice of the jurisdiction of the English courts usually follows suit. The European Union's favourable regimes of several recognition and enforcement of Judgments, especially the Brussels I Recast regulation, have made it even more attractive for member state's banks. But given that this regime changes after Brexit, will this privileged position of the UK be jeopardised?